2018
DOI: 10.1108/ijopm-10-2016-0595
|View full text |Cite
|
Sign up to set email alerts
|

The relationship regulator: a buyer-supplier collaborative performance measurement system

Abstract: The Relationship Regulator: a buyer-supplier collaborative performance measurement system 1. Introduction Over the years there has been a generalized tendency to increase management vision and control, with companies seeking to control over inter-firm processes and relationships. Several authors have therefore suggested that traditional intra-organizational performance measurement systems (PMSs) need to be broadened, with the development of external supply chain PMSs (SCPMSs), crossing company boundaries (Guna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…They findings of the study argued that the Interfacing purchasing helps a firm in strengthening the supplier relationship. Recently, Maestrini et al (2018), argued that the supplier and buyer collaboration in an interfacing purchasing function helps firm in improving the performance. Bag (2016) claimed the purchasing as an antecedent of supplier relationship, the findings of the Bag (2016) are consistent with the findings, as they claimed the purchasing as a determinant of supplier management.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…They findings of the study argued that the Interfacing purchasing helps a firm in strengthening the supplier relationship. Recently, Maestrini et al (2018), argued that the supplier and buyer collaboration in an interfacing purchasing function helps firm in improving the performance. Bag (2016) claimed the purchasing as an antecedent of supplier relationship, the findings of the Bag (2016) are consistent with the findings, as they claimed the purchasing as a determinant of supplier management.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…[24][25][26][27] From the practical perspective, PM system design, evaluation and applications have been well researched to support PM implementations in organizations. [28][29][30][31][32][33] An effective PM system enables project managers to quantify efficiency and effectiveness of past actions via PM activities to collect, sort, analyse and interpret PM results to support decision making processes. 34 Several recommendations for successful PM system design have been proposed from previous studies, such as PM should be positioned at a strategic level in organizations; selected measures should be clear and easy to understand by those being evaluated; performance data should be collected, where possible, by staff whose performance is being measured; performance should be reported daily or weekly; measures should consider all members of the organization so as to understand how they affect the entire business; PM systems feedback should be provided at numerous levels of the organization and PM systems feedback should be integrated cross-functionally to ensure it supports and not inhibits strategy implementation.…”
Section: Pmmentioning
confidence: 99%
“…Previous studies revealed the challenges and factors that facilitate inter-organizational performance measurement that involve different actors (Busi and Bititci 2006;Mahama 2006;Bititci et al 2007;Pekkola and Ukko 2016). According to Maestrini et al (2018), three factors should be considered in contemporary business environments. First, supply chains are becoming increasingly complex: Instead of being individual exclusive chains, supply chains appear as different types of networks where organizations collaborate in different types of relationships.…”
Section: Relational Mechanismsmentioning
confidence: 99%